Mechanistic Investigation of Osmium(VIII) Catalyzed Oxidation of Glutamic Acid With Sodium Salt of N-Chloro 4-Methylbenzenesulfonamide in Aqueous Media: A Practical Approach. Issue 1 (2nd January 2016) - Khan, Aftab Aslam Parwaz; Khan, Anish; Asiri, Abdullah M.; Azum, Naved; Rub, Malik Abdul; Rahman, Mohammed M.; Khan, Sher Bhadar
Abstract : L-glutamic acid is used in the production of monosodium glutamate spices and other biochemical reagents. Its oxidation kinetics and a detailed mechanistic interaction of Os(VIII) catalyzed Glue-CAT reaction in alkaline medium have been investigated at different temperatures. It has been studied spectrophotometrically as a basic experimental approach for this study. All variables affecting the development of the color were investigated and the conditions were optimized. The effect of Glue, CAT, Os(VIII), and OH concentration on the rate of reaction has been studied. The reactions follow identical kinetics for all It is a first order reaction in both Glue and CAT, but fractional order in alkali and Os(VIII). Increasing ionic strength dielectric constant of the medium had no significant effect on the rate. The effects of added products like halide ions and toluene-p-sulfonamide have also been investigated. A mechanism involving the formation of a complex between Glue-CAT-Os(VIII) has been proposed. The stoichiometry of the reaction is found to be 1:1. The main products of Glue were identified with the help of FTIR and TLC. The reaction constants involved in the mechanism are explained. There is a good agreement between the observed and calculated rate constants under different experimental conditions. Investigations at different temperatures allowed the determination of the activation parameters with respect to the slow step of the proposed mechanism. The proposed methods were successfully applied for the high yield of the products and short reaction times. It is also an inexpensive, simple, and smooth method.